Hyoid bone syndrome masquerading as temporomandibular joint dysfunction. Issue 5 (June 2019) - Jose, Anson; Nagori, Shakil Ahmed; Arya, Saurabh; Roychoudhury, Ajoy
Abstract: Hyoid bone syndrome is a type of cervicofacial pain that is caused by degeneration of the greater cornu of the hyoid at the attachment of the stylohyoid ligament. We report four patients who presented with deep-seated, dull, aching, temporomandibular (TMJ) pain that radiated from the greater cornu of the hyoid bone and did not respond to conservative management. Diagnostic tests included a local anaesthetic block and digital palpation of the greater cornu of the hyoid bone. All four patients responded well to methylprednisolone 40 mg/ml at the greater cornu of the hyoid bone, which resulted in complete resolution of their symptoms. No patients developed postoperative complications. Oral and maxillofacial surgeons involved in the treatment of orofacial pain should consider this less documented condition in their differential diagnosis when treating temporomandibular disorders.